Spiritual well-being and its predictors among Iranian adolescent girls, 2014-2015 - Mirghafourvand, Mojgan (International journal of children's spirituality, 2016)
Today, numerous studies are focused on spiritual well-being. This study aimed to determine the status of spiritual well-being and its predictors among adolescent girls. The participants in this cross-sectional study were 520 adolescents living in Tabriz, Iran. Samples were selected through cluster sampling method. The spiritual well-being' and socio-demographic characteristics' questionnaires were used. Multivariate linear regression was used to determine the predictors of spiritual well-being. The mean score of spiritual well-being was 90.22 (SD: 16.25), ranging from 20 to 120. Multivariate linear regression showed a significant relationship between spiritual well-being and the factors including parents' belief for their children's participation in religious ceremonies, sufficiency of family income for expenses and type of residence. The results show that the level of spiritual well-being in the girls is average to high, and considering the critical impact of spiritual well-being on the health, strategies are required to improve the adolescents' spiritual well-being.